Studi Temperatur Penyimpanan Pada Proses Penimbunan B30 Guna Mengurangi Korosi - Steven Johanes; Oksil Venriza; Bambang Sugito (Jurnal Ilmiah Teknik Kimia, 2021)
Pressure Vessel is a vessel to contain both liquid and gasses. The storage tank is one of the tools to contain fluid, so it is an important factor in an industry such as chemistry, oil, and power plants. Biodiesel is an alternative fuel made from vegetable oil that is environmentally friendly and can reduce exhaust emissions in diesel engines. Biodiesel is renewable and reduces engine performance, so it can be used as a solution to overcome the reduced fossil fuel reserves. It is necessary to determine the corrosion rate of biodiesel. This research was conducted by storing biodiesel in the sample tank for 0 day, 1 day, and 4 days after that, the ASTM D-130 copper strip corrosion test was carried out for 3 hours ± 5 minutes. From the research, we know that corrosion rate at indoor had been stored for 4 days and for outdoor at day 0,1 and 4 gets greater corrosion with result 1b( dark orange).